Prediction of excessively low vault after implantable collamer lens implantation using iris morphology - Khan, Muhammad Ahmad; Tan, Qian; Sun, Wei; Cai, Wang; Zhao, Libei; Lin, Ding (Frontiers in Medicine, 2022)
Purpose To identify the iris morphology-related factors for prediction of outcomes of excessively low vault (< 100 μm) after Implantable Collamer Lens V4c (ICL V4c; STAAR Surgical) implantation. Methods This retrospective case-control study included 81 eyes from 2,080 patients who underwent ICL implantation. Twenty-seven eyes of 27 patients with excessively low vault (< 100 μm) constituted the case group (excessively low vault group). Patients with vault (250 to 750 μm) were selected as the optimal vault group by matching anterior chamber depth, white-to-white distance and ICL size with cases with excessive low vault (< 100 μm) at a proportion of 1:2. The preoperative biometric parameters and postoperative vault were recorded. Multiple linear regression analysis was performed to assess the relationship between the postoperative vault and various variables. Conditional logistic regression analysis was used to estimate the risk factors for excessively low vault. Results The postoperative vault was associated with preoperative pupil diameter (PD), crystalline lens rise, iris concavity and the ratio of the iris concavity to chord length (P < 0.05). The larger iris concavity increased risk of excessively low postoperative vault (< 100 μm) (OR = 81.10; 95%CI = 2.87 to 2296.58; P = 0.01). Conclusions Eyes with obviously concave iris were associated with a higher rate of excessively low vault (< 100 μm). Evaluation of iris morphology may provide significant information for predicting excessive postoperative vault.